MODERASI PENDIDIKAN PESANTREN DI KALIMANTAN TIMUR - Khojir Khojir (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2020)
This article discusses the efforts of Islamic boarding schools to form educational moderation, models of moderation and the implications of pesantren education moderation. The design of this study was qualitative with a theological and pedagogical approaches. The informants of this research wre the leaders, religious teachers, administrators, and students. Furthermore, the data were collected through interviews, observations and documentation. To test the validity of the data, triangulation of data was performed. Data analysis was carried out in three stages, namely: reduction, presentation and conclusion drawing from the data. The findings of this study were; first, the pesantren efforts in shaping education moderation by socializing all forms of extremism and radicalism to the studensts, choosing teaching materials or books that are free from extremist values and radicalism, designing moderate curriculum and learning methods. Second, the education moderation model that integrates learning and collaboration with the life of pesantren. Third, the implications of educational moderation for pesantren were in forms of; positive community assessments of pesantren, increasingly moderate community, and making pesantren as a reference for the community.